N Response of No-Till Dryland Winter Triticale Forage - Vigil, Merle F.; Poss, David J. (Communications in Soil Science and Plant Analysis, 2016)
Triticale's forage-yield response to fertilizer nitrogen (N) is impressive on soils testing low in available N. Our objectives were to (1) quantify the forage-yield response of dryland winter triticale to applied N and residual nitrate N and (2) fit the yield data to a regression equation based on both applied N and residual soil nitrates and use the fitted equation to calculate economic optimum N rates for this crop (EONR). Winter triticale was direct seeded no-till into wheat or millet stubble for four site years at the United States Department of Agriculture, Agricultural Research Service (USDA-ARS) Central Great Plains Research Station. In each experiment (1995, 2007, 2009 and 2010) just prior to planting, the soil was sampled for nitrate-N. Replicated field plots were top-dressed with 0, 22, 34, 67, 90, 101 or 135 kg of N fertilizer per ha as urea-N. Yield and total biomass N was then measured in each plot in late spring each year. A relative yield N response equation, fitted to all four years of data, was able to explain 93% of the variability in yield. That equation provided reasonable EONR estimates that matched 87% of the EONRs calculated for individual years.